Here it goes:
Remember from math that equations could be structured in function notation:
f(x) = [something],where f(x) would be pronounced f of x; the 'of' being important for this puzzle.
Building on this concept replace the 'f' with x itself. Doing so one gets:
x(x) = [something] or x of x = [something]
(Hang in there...it'll be worth it.)
Given that, here are the rules of the puzzle:
Create as many logical word equations of the format x of x = [something] such that [something] is a legitimate word, as per dictionary.com or answers.com, comprised of only the letters represented in word x; either in part or in whole . The new [something] word can only utilize the unique instances of the letters in x. (Rule 1)
For example, the following would not be allowed:
shuffle of shuffle = lushesbecause the 's' was used twice.
In addition the [something] word must make logical sense in the context of the word equation (Rule 2).
Going back to 'shuffle' above, a shuffle of the word results in a word that has all of the letters, s-h-u-f-f-l-e, to be logically correct. The word 'lush' would satisy Rule 1 but not Rule 2.
Another example of [something] that would be creative but not logical would be:
typo of typo = tpyo; because tpyo is not a legitimate word.
Here are a few examples to get you started with many more in the comments (don't peek until you've given it a try first):
something of something = some
something of something = thing
something of something = me
something of something = toe
something of something = hinge
something of something = hinges
something of something = sing
something of something = go
something of something = something
something of something = ...
Here are some more examples with the 'function' notation utilzed for brevity; remember x(x) is x of x:
all(all) = all
bit(bit) = it
eclipse(eclipse) = lip
eclipse(eclipse) = clip
slice(slice) = lice
four(four) = four
half(half) = ha
ignorant(ignorant) = ignorant
last(last) = last
laststraw(laststraw) = straw
lastquarter(lastquarter) = quarter
snip(snip) = nip
piece(piece) = pie
Add any solutions that you find in the comments.